Implementasi Model Student Facilitator and Explaining pada Pembelajaran Tematik Terpadu Di SD - Hajar, Siti; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This research aims to implement the use of the Student Facilitator and Explaining cooperative model in integrated thematic learning in elementary schools. And to see the effect on learning outcomes. This type of research is descriptive research with qualitative methods, because it is done to search for data and facts. After the data is collected then it is presented in the form of a sentence which is then drawn conclusions based on the facts seen. Based on the learning results obtained by the researcher, after conducting the research, it showed that of the total students, only 7% of students or 6 students had scores below the minimum completeness value. Meanwhile, the other 93% or 22 other people have high scores. With an average value of 89. From this it can be concluded that the Student Facilitator and Explaining learning model has a very good influence on learning outcomes. Supported by the use of the Student Facilitator and Explaining model of learning steps in the learning process.